Kapabilitas Dinamis Berbasis Budaya dalam Tata Kelola Pengembangan Destinasi Pariwisata Gunungkidul - Dyah Mustika Wardani; Lilik Edi Saputro; Gilang Fahreza; Dwi Yoso Nugroho; Joko Triyono (Jurnal Ilmiah Pariwisata, 2026)
This study aims to examine culture-based dynamic capabilities in the governance of tourism destination development in Gunungkidul. A qualitative approach with a case study design was employed to explore the complex interactions between local culture, adaptive capabilities, and multi-stakeholder governance. Data were collected through purposive sampling, in-depth interviews, and participant observation involving tourism village managers, government officials, tourism entrepreneurs, community leaders, and local communities. The data were analyzed using thematic analysis, including transcription, coding (open, axial, and selective), categorization, and interpretation. The findings reveal that cultural values such as mutual cooperation (gotong royong), social trust, and local wisdom play a significant role in shaping the destination’s dynamic capabilities. These capabilities are reflected in three dimensions: sensing (identifying tourism opportunities through local knowledge), seizing (developing community-based tourism innovations), and transforming (adapting institutional structures and governance practices). Despite challenges such as coordination gaps and uneven institutional capacity, local culture strengthens stakeholder collaboration through a combination of formal and informal governance mechanisms. This study proposes an integrative model: Culture → Dynamic Capabilities → Governance → Sustainable Tourism Development, and provides practical insights for policymakers to integrate cultural values in enhancing destination resilience and competitiveness. Keywords: dynamic capabilities, culture, governance, sustainable tourism, Gunungkidul